Skewed Invariant Natural Killer T (iNKT) Cells, Impaired iNKT:B Cell Help and Decreased SAP Expression in Blood Lymphocytes from Patients with Common Variable Immunodeficiency (2017)
ABSTRACT: Common variable immunodeficiency (CVID) is a syndrome with predominantly defective B cell function. However, abnormalities in the number and function of other lymphocyte subpopulations in peripheral blood (PB) have been described in most patients. We have analysed the distribution of iNKT cell subpopulations in the PB of CVID patients and the ability of these cells to provide in vitro cognate B cell help. The total of iNKT cells was reduced in the PB of CVID patients, especially CD4+, CD4-/CD8- and CCR5+/CXCR3+. These findings were associated with an enrichment of memory-like and a tendency towards a reduction in TNF-a-expressing effector iNKT cells in the peripheral blood mononuclear cells (PBMC) of CVID patients. Moreover, an accumulation of follicular helper iNKT cells in the PB of CVID patients was demonstrated. CVID aGalCer-pulsed iNKT cells are not able to induce autologous B cell proliferation although they do induce proliferation to healthy donor B cells. Interestingly, autologous and heterologous co-cultures did not differ in the amount of immunoglobulin secreted by B cells in vitro. Finally, reduced intracellular SAP expression in iNKT cells and other lymphocytes in the blood from CVID patients was observed. These results provide further insights into the immunological mechanisms underlying the iNKT cell defects and the potential targets to improve B cell help in CVID.